An Identity-Based Cross-Domain Authenticated Asymmetric Group Key Agreement - Qingnan Chen; Ting Wu; Chengnan Hu; Anbang Chen; Qiuhua Zheng (Information, 2021)
Cross-domain authenticated asymmetric group key agreement allows group members in different domains to establish a secure group communication channel and the senders can be anyone. However, the existing schemes do not meet the requirement of batch verification in the group key negotiation phase, which makes the schemes have low efficiency. To address this problem, an identity-based cross-domain authenticated asymmetric group key agreement is proposed that supports batch verification. The performance analysis shows that this protocol is highly efficient. Finally, the proposed protocol is proved to be secure under the k-Bilinear Diffie–Hellman Exponent assumption.